Using Story Mapping Technique in Teaching Reading of Narrative Text for Junior High School Students - Imana Annisa; Witri Oktavia (Universitas Negeri Padang, 2020)
This paper is aimed at describing the use of ‘Story Mapping’ to improve students’ comprehending in reading narrative text at junior high school students. This technique is applied to help junior high school students to understanding andcomprehending narrative text. This technique enables students to solve the problem by using story mapping sheet given to them. By using this technique, the students are allowed to read the narrative text and determine the appropriate part of the text to each part of the sheet on story mapping.